2016
DOI: 10.1021/acs.est.6b00876
|View full text |Cite
|
Sign up to set email alerts
|

Survivability, Partitioning, and Recovery of Enveloped Viruses in Untreated Municipal Wastewater

Abstract: Many of the devastating pandemics and outbreaks of the 20th and 21st centuries have involved enveloped viruses, including influenza, HIV, SARS, MERS, and Ebola. However, little is known about the presence and fate of enveloped viruses in municipal wastewater. Here, we compared the survival and partitioning behavior of two model enveloped viruses (MHV and ϕ6) and two nonenveloped bacteriophages (MS2 and T3) in raw wastewater samples. We showed that MHV and ϕ6 remained infective on the time scale of days. Up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
572
3
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(605 citation statements)
references
References 59 publications
24
572
3
6
Order By: Relevance
“…45 A T90 value (i.e., time to reach 90% inactivation) of 121 hours MS2 in unpasteurized wastewater at 25 °C was reported in a previous study. 46 The decrease in Phi6 concentration in the converging sewer pipes model is larger compared to that in earlier studies on the persistence of Phi6 in wastewater and the inactivation of Ebola virus in sterilized wastewater. 19 The differe nce may be due to the effect of heat inactivation inside the sump pump, used for flow circulation in the sewer model, as Phi6 is believed to be more sensitive to higher temperature.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…45 A T90 value (i.e., time to reach 90% inactivation) of 121 hours MS2 in unpasteurized wastewater at 25 °C was reported in a previous study. 46 The decrease in Phi6 concentration in the converging sewer pipes model is larger compared to that in earlier studies on the persistence of Phi6 in wastewater and the inactivation of Ebola virus in sterilized wastewater. 19 The differe nce may be due to the effect of heat inactivation inside the sump pump, used for flow circulation in the sewer model, as Phi6 is believed to be more sensitive to higher temperature.…”
Section: Discussionmentioning
confidence: 68%
“…20 The finding that heat inactivation only applies to Phi6 is consistent with the general finding of greater susceptibility of enveloped viruses to inactivation. 46 The large difference in airborne concentrations of MS2 and Phi6, a factor of >100, in both the aeration basin and sewer model can be attributed to two causes. First, their different inactivation and absorption rates results in different final concentrations in the mixed liquor even though they were spiked at the same initial concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, Elving et al (99) showed that MS2 was more persistent than the enveloped dsRNA phage ⌽6 and the enveloped ssRNA influenza A virus during composting of manure at 35 to 55°C. Similarly, Ye et al determined that, independent of genome type, enveloped viruses (ssRNA murine hepatitis virus and dsRNA phage ⌽6) were inactivated at higher rates than naked viruses (MS2 and dsDNA phage T3) in wastewater (100). In contrast, Emmoth et al (17) did not observe a significant influence of the envelope among ssRNA virus inactivated in manure at 4 to 25°C.…”
Section: Discussionmentioning
confidence: 98%
“…Sink 1, on the other hand, was farthest away from the source (sink 5), and its P-trap had the greatest incline in the drain line connecting the sinks, which could perhaps contribute to the reasons there was no GFP-expressing E. coli colonization detected in it after 7 days. There has been more investigation about microbiologic dynamics of infectious viral particles such as those of severe acute respiratory syndrome (SARS) and Ebola viruses through premise plumbing systems (34)(35)(36). However, the microbiology, sustainability, and dynamics might be very different, although the backflow and inoculation issues could have some parallels when comparing viruses to bacteria.…”
Section: Discussionmentioning
confidence: 99%